ASPECTS OF PROVING IN THE FIELD OF COMBATING AGAINST TRADING OF ILLEGAL ALCOHOLIC BEVERAGES IN THE ADMINISTRATIVE PROCESS - Trofimovs, Igors (Administrative and Criminal Justice, 2016)
The author of the paper dealt with the historical origin of alcoholic beverages; clarified the concept of legal and illegal alcohol, factors and causes of its consumption. The author studied also the legal and practical aspects of getting evidences/ proofs in the field of combatting against trading of illegal alcoholic beverages. As the result of the research, the author recognizes as essential that the normative legislation of the Republic of Latvia takes the greatest emphasis on the tax range, instead of protecting society from the alcohol of poor quality. There is a large demand for cheap and available illegal alcoholic beverages in the country. Small fines (compared with profit gained) imposed on illegal alcohol producers, traders and holders of retail premises, passivity of local authorities make a bad influence on distribution of illegal alcohol. The State Police has not worked out any instructions, any methodological guidance relating the way, how the inspections are carried out and how evidences at the trading spaces are collected. Other negative factors are an unproductive inter-institutional cooperation, passivity of the population in cooperation with the Police and incomplete legislation.